PENENTUAN KAPASITAS SIMPAN SHALE GAS PADA SUMUR “R26”, LAPANGAN “RKO - Ohorella, Ramdhan; Effendi, Dahrul; Triaji, Nandang (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2024)
Global demand for oil and gas is projected to increase by 6% from 2022 to 2028, reaching 105.7 million barrels per day (bopd), driven by strong demand from the petrochemical and aviation sectors. Consequently, exploration is needed to discover new oil and gas reserves, with attention shifting to unconventional resources, considering the depletion and challenges in finding conventional reserves. This study aims to analyze the adsorption behavior of five shale rock samples from the